Evaluation Strategy to Improve the Utilization of Posbindu As-Syifa I in the Facilities Aspect in Gerem Village, Banten Province - Firda Diah Utami; Dasrun Hidayat; Yen Efawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study analyzes the implementation of service strategic management at Posbindu PTM As-Syifa I in Gerem Village, Banten Province, focusing on service quality, monitoring and evaluation systems, and the role of human resources and stakeholders. Using descriptive qualitative methods through in-depth interviews, observations, and document studies. Results show service quality is quite good with active cadre support and basic screening tools. However, limited infrastructure, absence of permanent facilities, and participant fluctuations remain obstacles. Monitoring and evaluation are conducted through primary health center supervision but lack structured internal evaluation mechanisms. SWOT analysis indicates the need for strengthening internal evaluation SOPs, cadre capacity building, and digitalization of recording. Limited funding and unintegrated stakeholder coordination emphasize the importance of formal cooperation and funding diversification for program sustainability.